"Art is Seeing Things": Ekphrastic Education in Ali Smith's Seasonal Quartet. Issue 2 (17th February 2022) - Schmitz-Justen, Laura
ABSTRACT: By staging ekphrastic encounters with self-reflexive art Ali Smith's Seasonal Quartet both models and advocates for a mode of engagement with the socio-political present that requires a critical look at dominant narratives. The ekphrastic encounters the novels stage serve as meta-fictional commentary that suggests that art can facilitate engagement with other perspectives and teach a benign mode of looking that could provide a way into more compassionate and open societal dialogue. However, the Quartet articulates scepticism as to whether its ekphrastic lessons will be heeded, particularly under the current attention economy and institutionalised dismissal of the arts. Specifically, by centring questions of composition Smith's ekphrastic encounters with collage address the politics of representation whereas the sculptural encounters bring out themes of endurance and passive resistance as political stategy. It is thus not only the state of the nation Smith sheds light on but also the state of the novel.